Herbicidal weed management in dual purpose tall wheat (Triticum aestivum) - SANGWAN, MEENAKSHI; HOODA, V S; SINGH, JAGDEV; DUHAN, ANIL (The Indian Journal of Agricultural Sciences, 2019)
The field efficacy of pre- and post-emergence herbicide combinations for control of complex weed flora in dual purpose tall wheat was evaluated in a field study conducted at Research farm of CCS HAU Hisar (Haryana) during rabi of 2015-16 and 2016-17. Phalaris minor Retz., Rumex dentatus L., Convolvulus arvensis L., Medicago denticulata Willd., Cirsium arvense (L). Scape, Cyperus rotundus L. etc. were major weeds in experimental area. Application of herbicides in both growing seasons reduced weed density and increased wheat grain yield as compared with weedy. After cutting of wheat for fodder, total weed density was reduced under application of pendimethalin 1500 g/ha PRE fb pinoxaden + metsulfuron (50+4) 2 WAC (week after cutting at 55 DAS), pendimethalin 1500 g/ha PRE fb sulfosulfuron+ metsulfuron (30+2) 2 WAC and pendimethalin 1500 g/ha PRE fb clodinafop + metsulfuron (60+4) 2 WAC as compared to alone application of post emergence herbicides. During 86-115 DAS period, more crop growth rate was observed under sequential application of herbicides as compared to post-emergence herbicides. Among herbicidal treatments, significantly higher leaf area index, crop dry weight, grain yield and B:C ratio was reported under sequential application of herbicides which were significantly higher than weedy and alone pre- and post-emergence application of herbicides during both the years of study.